2021
DOI: 10.1039/d1se00540e
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale hydrotreating of catalytic fast pyrolysis biocrudes: process performance and product analysis

Abstract: Catalytic fast pyrolysis (CFP) is a technology option for producing advanced biofuels from hydrocarbon-rich biocrude intermediates. The relatively high oxygen content of biocrudes compared to petroleum intermediates increases hydrogen consumption...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Although successful hydrotreatment of bio-oils in fixed bed reactors has been reported previously, several issues were noted during these studies, such as catalyst deactivation, plugging, or coke formation in the reactors . Potentially, plugging may even occur in the heated transfer lines to the reactors.…”
Section: Resultsmentioning
confidence: 94%
“…Although successful hydrotreatment of bio-oils in fixed bed reactors has been reported previously, several issues were noted during these studies, such as catalyst deactivation, plugging, or coke formation in the reactors . Potentially, plugging may even occur in the heated transfer lines to the reactors.…”
Section: Resultsmentioning
confidence: 94%
“…Upgrading pyrolysis and HTL oils to transportation fuels via hydrotreating is one route under development that could open a large market, but catalyst deactivation during upgrading remains a major challenge 103,108,109 . Additionally, it requires a considerable amount of H 2 .…”
Section: Direct Liquefaction Of Waste Materialsmentioning
confidence: 99%
“…Upgrading pyrolysis and HTL oils to transportation fuels via hydrotreating is one route under development that could open a large market, but catalyst deactivation during upgrading remains a major challenge. 103,108,109 Additionally, it requires a considerable amount of H 2 . Another suggested pathway is co-processing such oils in fluid catalytic cracking (FCC) units, but it is hindered by concerns about incompatibility of these oxygenate-rich Samples provided under an agreement that prohibits disclosing the supplier.…”
Section: State Of Biomass and Waste Liquefaction Technologymentioning
confidence: 99%
“…In contrast, a recent study reported that several biocrudes produced from catalytic biomass pyrolysis were upgraded with varying degrees of success. 42 Three of the CFP biocrude feeds had similar oxygen content (25−29 wt %). The feed with the highest oxygen content also had the highest concentrations of levoglucosan and carboxylic acids.…”
Section: ■ Summary and Conclusionmentioning
confidence: 99%
“…RCFP biocrude was hydrotreated in a pilot-scale hydroprocessing unit to produce advanced hydrocarbon biofuels and blendstocks. A summary is provided of the design and operation of this unit that has been described in more detail in the recent literature. The hydroprocessing unit consists of five main sections: (1) an oil feed system equipped with pumps and flow control, (2) a gas feed system, (3) a reactor system, (4) a gas–liquid separator system, and (5) a gas and liquid sampling system.…”
Section: Pilot-scale Hydrotreating Reactor Systemsmentioning
confidence: 99%